Influence of cohort effects on patterns of suicide in England and Wales, 1950-1999 - Gunnell, David J.; Middleton, Nicos; Whitley, Elise; Dorling, Danny F L; Frankel, Stephen J. (My University, 2003)
Background: Age- and gender-specific suicide ratesin England and Wales have changed considerably since 1950. Aims: To assess whether cohort effects underlie some of these changes. Method: Graphical displays to assess age-period-cohort effects on suicide for the period 1950-1999. Results: Successive male birth cohorts born after 1940 carried with them, as they aged, a greater risk of suicide than their predecessors although this effect diminished for the 1975 and 1980 birth cohorts.There was less clear evidence of any increased risk of suicide in post-war female birth cohorts. Conclusions: Succeeding generations of males born in the post-war years have experienced increasing rates of suicide at all ages, an observation in keeping with patterns seen in other countries. If these trends continue into middle- and old-age they will lead to a great increase in overall male suicide rates.
Keywords: Suicide; Age-period-cohort